An analysis of household acceptance of curbside recycling scheme in Kuala Lumpur, Malaysia. (June 2015) - Zen, Irina Safitri; Siwar, Chamhuri
Abstract: This study explored and analyzed household acceptance of the curbside recycling scheme (CRS) in selected residential areas in Kuala Lumpur, Federal Territory (KLFT), Malaysia where the number of drop-off recycling facilities are limited. The analysis identified the socio-economic factors that affect the respondents' willingness to pay (WTP) for CRS. A survey using standardized questionnaires of the contingent valuation method (CVM) was administered to 460 households. The proposed scheme received a positive response with high willingness of residents to separate (90%) but low WTP (34%) for the scheme charges. Despite the average of WTP curbside recycling charges of MYR88.80 added to household annual tax has translated into MYR7.40 per month (USD 2.50), the study revealed various issues to improve existing recycling facilities with the solid waste management (SWM) and recycling practices. The analysis further revealed that CRS gained support from the Chinese who practice recycling and also from older age groups with the involvement of other family members such as a father/husband and adult and household who has the right attitude towards recycling. It showed the demand for more convenient recycling services which is an improvement from drop-off recycling facilities or a public recycling facilities to a private recycling services at the household level. Finally, CRS has potential application in the middle-high income residential areas of Bangsar and Wangsa Maju. Highlights: Household acceptance of curbside recycling scheme (CRS) in selected residential areas with limited number of drop-off recycling facility in Kuala Lumpur, Malaysia has been analyzed. Socio-economic factors affect the respondents' willingness to pay (WTP) for CRS with high response for willingness to separate (90%) but low WTP (34%). Charging through CRS was opposed by 59% of the respondents whose reveals the various issues in integrating CRS with solid waste management in Malaysia. CRS gained supports from the Chinese who practice recycling and also from older age groups and household who has the right attitude towards recycling. CRS has potential application in selected middle-high income residential areas in Kuala Lumpur despite the informal recycling and community based organization, CBOs in recycling activity.